2017
DOI: 10.1007/978-3-319-57613-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Immune Function of Cardiac Fibroblasts

Abstract: This chapter will discuss the role of cardiac fibroblasts as a target of various immunological inputs as well as an immunomodulatory hub of the heart through interaction with immune cell types and chemokine or cytokine signaling. While the purpose of this chapter is to explore the immunomodulatory properties of cardiac fibroblasts, it is important to note that cardiac fibroblasts are not a homogeneous cell type, but have a unique embryological origin and molecular identity. Specific properties of cardiac fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 187 publications
0
7
0
Order By: Relevance
“…On the other hand, by their biophysical interactions with cardiomyocytes through mechanical or electrical junctions, fibroblasts can facilitate electro-mechanical transduction important for the proper maintenance of the conduction system (74, 75). Upon insult, fibroblasts initiate production of ECM components for tissue reconstruction (76) and transmit signals to surrounding cardiomyocytes, but also to other stromal cells for initiation of the healing process (23, 7779). However, alterations of fibroblast behavior in response to extrinsic factors, such as inflammatory cytokines, and persistent activation lead to deregulated matrix deposition and consequently to the formation of fibrotic tissue, underlining the pivotal role of fibroblasts in regulating the equilibrium between disease development and tissue repair and regeneration in the heart (70, 8082) and other tissues (8385).…”
Section: Cardiac Subpopulations and The Contribution Of Innate Immunitymentioning
confidence: 99%
“…On the other hand, by their biophysical interactions with cardiomyocytes through mechanical or electrical junctions, fibroblasts can facilitate electro-mechanical transduction important for the proper maintenance of the conduction system (74, 75). Upon insult, fibroblasts initiate production of ECM components for tissue reconstruction (76) and transmit signals to surrounding cardiomyocytes, but also to other stromal cells for initiation of the healing process (23, 7779). However, alterations of fibroblast behavior in response to extrinsic factors, such as inflammatory cytokines, and persistent activation lead to deregulated matrix deposition and consequently to the formation of fibrotic tissue, underlining the pivotal role of fibroblasts in regulating the equilibrium between disease development and tissue repair and regeneration in the heart (70, 8082) and other tissues (8385).…”
Section: Cardiac Subpopulations and The Contribution Of Innate Immunitymentioning
confidence: 99%
“…Studies in murine models have identified that cardiac fibroblasts make up close to 25% of the heart tissue ( 17 ). While not possessing electrical or contractile functions themselves, cardiac fibroblasts can couple to cardiomyocytes to aid in the propagation of electrical signals, maintain extracellular matrix homeostasis, and secrete cytokines and chemokines to modulate the immune system ( 18 , 19 ). After injury, these fibroblasts exhibit functions to remodel the ECM, alter chemical and mechanical signals, participate in angiogenesis, and contribute to fibrosis ( 20 , 21 ).…”
Section: Fibroblast To Myofibroblast To Osteoblast-like Cellmentioning
confidence: 99%
“…DAMPS alert the immune system of the tissue damage through activation of pattern-recognition receptors (PRRs) present in immune cells as well as in structural cells such as cardiomyocytes, fibroblasts, and endothelial cells 16,3,4 . PRR activation on fibroblasts induces their proliferation, migration, differentiation into myofibroblasts [G] , ECM turnover, and production of fibrotic and inflammatory factors 18,[19][20][21][22][23] . Crucial PRRs involved in the response to myocardial ischaemia are Toll-like receptor (TLR) 2 and TLR4 and the receptor for advanced glycosylation end products (RAGE) 24 .…”
mentioning
confidence: 99%
“…In the injury context, cardiac fibroblasts respond to immunological stimuli and signal to cardiomyocytes 8 , a crucial role in the orchestration of the healing process. Fibroblasts themselves have broad immune-regulatory properties, interpreting inflammatory factors to signal surrounding stromal cells and initiate production of ECM components for tissue reconstruction20 .…”
mentioning
confidence: 99%